سلسلہ چشتیہ سے متعلق ڈاکٹر نثار احمد فاروقی کی تحقیقات کا مطالعہ: A Study of Dr. Nisar Ahmed Farooqui's Investigation Related to Chishti Order of Sufism (Al-Qamar, 2021)
Dr. Nisar Ahmad Farooqi was a multipartite personality. He was well known researcher of Urdu. In Urdu language and literature, he recognized his status as a critic, translator, writer poet and observer. He had a special affinity with Sufism especially the Chishti order. He wrote explanatory articles on related literature (Malfozāt) of Chishti order to make a positive change in the society by popularizing the teachings of the Chishti Sufis. This article reviews their research work about Sufism. He presented the cover of various discussions of Sufism. According to him, the Chishti teachings are the solution to the anxiety and chaos of the present age. He wrote biographical articles on Chishti Sufis, avoiding exaggeration and also identified new sources of research regarding this. His research regarding the tomb of Muhammad Yaqoob son of Baba Farid Ganjshakr is valuable. To understand the spirit, method and scope of Islamic Sufism, a study of his research can be beneficial.
Keywords: Sufism; Chishti order; investigations; Nisar Ahmad Farooqi